Pengaruh Latar Belakang Pendidikan terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Intervening pada Dinas Energi dan Sumber Daya Mineral Provinsi Jambi - Endang Tri Rahayu; Sry Rosita; Rohman Wilian (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to describe and analyze the effect of educational background on employee performance through work motivation as an intervening variable at the Energy and Mineral Resources Office of Jambi Province. The method used is quantitative analysis with a population of 64 employees and a sample of 63 respondents selected using a saturated sampling technique. Data were collected using a Likert scale-based questionnaire, and the analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS 3 software. The results showed that: (1) educational background has a positive and significant effect on employee performance, (2) educational background has a positive and significant effect on work motivation, (3) work motivation has a positive and significant effect on employee performance, and (4) work motivation acts as an intervening variable that mediates the effect of educational background on employee performance. Based on the results, it is recommended that the Energy and Mineral Resources Office of Jambi Province organize relevant technical training related to their work areas, professional certification, and training based on actual work needs. It is also suggested to pay special attention to the quality of employee work, one strategy being continuous training focused on improving work accuracy, quality management, and more detailed and measurable standard operating procedures (SOPs). For work motivation, more attention should be given to providing opportunities for personal development, such as advanced skills training, opportunities for innovation in work, and involving employees in strategic decision-making according to their capacity.